A compendium of specific histopathological bodies in dermatology - Anup Kumar Tiwary; Hiral Shah; Bhushan Madke; Piyush Kumar (Wolters Kluwer Medknow Publications, 2021)
The spectrum of histopathological variations of most of the Dermatological conditions is so wide and overlapping that even with our current vast knowledge of this discipline, it seems to be a tough task for clinicians as well as Dermatopathologists to arrive at a conclusive diagnosis in many cases. However, with the aid of special stains and advanced diagnostic techniques, some characteristic histopathologic features have been defined over the time, among which histopathological bodies or inclusion bodies serve as specific clues. With this perspective in view, an attempt has been made to collate and describe the well-known as well as the lesser-known histopathological bodies seen in various dermatological diseases. The underlying pathogenesis and ultramicroscopic features of these structures have also been outlined in brief.